Intrinsic fluorescence‐based at situ soft sensor for monitoring monoclonal antibody aggregation. (22nd July 2015) - Ohadi, Kaveh; Legge, Raymond L.; Budman, Hector M.
<x xml:space="preserve">Abstract</x> Intrinsic fluorescence spectroscopy, in conjunction with partial least squares regression (PLSR), was investigated as a potential technique for online quality control and quantitative monitoring of Immunoglobulin G (IgG) aggregation that occurs following exposure to conditions that emulate those that can occur during protein downstream processing. Initially, the impact of three stress factors (temperature, pH, and protein concentration) on the degree of aggregation determined using size exclusion chromatography data, was investigated by performing a central composite designexperiment and applying a fitting response surface model. This investigation identified the influence of the factors as well as the operating regions with minimum propensity to induce protein aggregation. Spectral changes pertinent to the stressed samples were also investigated and found to corroborate the high sensitivity of the intrinsic fluorescence to conformational changes of the proteins under study. Ultimately, partial least squares regression was implemented to formulate two fluorescence‐based soft sensors for quality control—product classification—and quantitative monitoring—concentration of monomer. The resulting regression models exhibited accurate prediction ability and good potential for in situ monitoring of monoclonal antibody downstream purification processes. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1423–1432, 2015